2022
DOI: 10.1503/cjs.019419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a surgical observership on the perceptions and career choices of preclinical medical students: a mixed-methods study

Abstract: Background: Medical students are increasingly choosing nonsurgical specialties; observership programs can address factors influencing them toward surgical careers by allowing preclerkship exposure and mentorship, and correcting misconceptions. The aims of this study were to assess the influence of a peer-led observership program at the Université de Montréal on the career choices of preclinical medical students and to determine the factors associated with a positive observership experience. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Hamid .S et al Contrary, in the US, a recent study states that more than 80% of students chose surgery as a future choice during observer ship, most of whom are females. 14,15 In the present study, 47% of individuals planned to complete residency abroad, while a recent study done in Peshawar reported that 39% of nal-year students would like to complete residency abroad. 16 Another study in Peshawar reported that 53% of individuals set caveats for postgraduation abroad.…”
Section: Discussionmentioning
confidence: 47%
“…Hamid .S et al Contrary, in the US, a recent study states that more than 80% of students chose surgery as a future choice during observer ship, most of whom are females. 14,15 In the present study, 47% of individuals planned to complete residency abroad, while a recent study done in Peshawar reported that 39% of nal-year students would like to complete residency abroad. 16 Another study in Peshawar reported that 53% of individuals set caveats for postgraduation abroad.…”
Section: Discussionmentioning
confidence: 47%